Method for Remote State Identification Snow-Ice Cover by the Ratio of Fresnel Reflection Coefficients - V. G. Mashkov (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. Currently, the development of safe helicopter landing systems as the most complex and dangerous stage of a flight is one of the priority tasks. A significant number of companies in Russia and abroad are engaged in its solution. Landing on unprepared (unequipped) sites with snow-ice cover may be caused by the need to deliver units, cargo and ammunition in combat conditions, search and rescue operations, evacuations of victims, etc. A key factor for a landing decision is information about the height of snow and about the depth of ice cover. In the paper remote identification of the state of snow-ice cover, excluding the need to present any person (crew member or rescue worker) on a landing site is proposed.Aim. To develop a method for the remote identification of the state of snow-ice cover used to determine the possibility of a helicopter - type aircraft safe landing on a reservoir with snow-ice cover.Materials and methods. Numerical simulation of echo signals Fresnel reflection coefficients polarization ratio was realized in MatLab. Vertical and horizontal polarizations in the range from 25 to 45 degrees were simulated.Results. Intervals of polarization relations correspond to the interval density of snow-ice layers for fixed angles. For example, when θ = 34 for dry snow ρds = 100…500 kg/m3 (ε'ds = 1.162…1.984) – Prm = 5.6915...3.3266, dry firn ρdf = 500…700 kg/m3 (ε'df = 1.984…2.51) – Prm = 3.3266...2.8311, dry ice ρdi = 700…913 kg/m3 (ε'di = 2.51…3.179) – Prm = 2.8311...2.4753. A layer reconstruction inverse problem was solved by indirect determining of complex relative permittivity of each successive underlying layer with 10-2 real part resolution. The identity of the obtained characteristics of snow-ice layers with calculated (standard) values was established.Conclusion. Remote identification of components of a snow-ice cover structure allows one to automate the process of evaluating of landing possibility. Thereby it reduces a decision-making time and increases a level of safety. In contrast to the known methods of identification of the surface layer the identification of multilayer medium layers was carried out.